The Role of Strength and Conditioning in the Prevention and Treatment of Chronic Lateral Ankle Instability. Issue 2 (22nd April 2022) - Young, Kaycie L.; Morris, Brandon; Herda, Trent J.
ABSTRACT: Lateral ankle sprains are one of the most common injuries sustained during sport or physical activity. Up to 40% of individuals can develop chronic lateral ankle instability (CLAI) after a lateral ankle sprain. CLAI occurs when functional or mechanical insufficiencies of the lateral ankle ligamentous complex persist. The purpose of this article is to identify characteristics of CLAI and describe strength and conditioning strategies that can be used to treat lateral ankle ligamentous injuries, preventing them from progressing on to CLAI (See Video, Supplemental Digital Content 1, http://links.lww.com/SCJ/A306 ).